O Papel do ESG no Value Relevance e Gerenciamento de Resultados em Companhias Latino-Americanas - Santos, Geovane Camilo dos (2023)
This thesis aims to analyze the relationship between environmental, social, and corporate governance (ESG) with earnings management and value relevance. The sample consists of 1,419 observations of Latin American companies for the time period from 2010 to 2021. Data were collected from the Refinitiv Eikon® platform and processed using an unbalanced panel and Wilcoxon test. The results revealed that companies with a higher level of ESG exhibit a higher level of earnings management, suggesting that they seek to maintain their reputation by disclosing more ESG information. The results also showed that entities with higher ESG have a lower stock price. This result can be explained by organizations disclosing ESG practices to create a good reputation in the market (positive relationship between ESG and earnings management) and due to ESG being still recent in this region, where users prefer to consider financial metrics, which have been the most relevant for years. Companies with a higher level of earnings management were those that had a lower level of stock price, meaning that when the information is of lower quality, there is a tendency for a reduction in the price of their shares. The interaction of ESG and earnings management showed only one significant relationship, which was negative, meaning that when the organization presents higher ESG in the presence of higher earnings management, it tends to have a lower stock price. The analyses were also performed considering the period with and without the pandemic. It was found that before the pandemic, a negative relationship between ESG and earnings management occurred, and after the start, the relationship was positive. This may indicate that managers took advantage of the moment of greater turbulence to disclose more ESG practices with the purpose of hiding information with higher levels of discretionary practices (according to the Wilcoxon test). Earnings management showed a positive and significant relationship with stock price in the Jones (1991) model after the start of the pandemic. The relationship between ESG and stock price and the interaction between ESG and earnings management were not significant. The thesis can contribute to investors by indicating whether the increase in ESG information is linked to lower quality of accounting information. Thus, investors have indications that the increase in ESG practices in this region, on average, indicates that managers are disclosing information with more earnings management practices and that higher ESG values also reduce the stock price. In the academic realm, the study differs from others, as the antecedents analyze the relationship between ESG and earnings management and ESG and stock price separately, while this thesis performed the interaction to verify if ESG is capable of reducing earnings management and thus increasing the stock price, seeking to deepen the understanding of the Stakeholder Theory. Therefore, the proposed thesis was partially accepted, as ESG increased earnings management in two models, earnings management reduced stock price in all models, and the interaction between ESG and earnings management reduced stock price in only one model.